Akad Tidak Bernama Dalam Hukum Kontrak Bisnis Syariah - Rudiansyah Rudiansyah; Syaiful Anam (Jurnal Keislaman, 2023)
Studying unnamed contracts is an important requirement for economic business actors, especially sharia economic actors. The rapid development of the economy and business requires business actors to study unnamed contract forms in sharia business practices in order to respond to the challenges of the times. This research will examine unnamed contracts in sharia business contract law. This type of research is library research, which is a study by examining data from various literature. The results of the study show that unnamed contracts are contracts that are not specifically regulated in fiqh books and do not have special provisions. This contract is made and determined by the parties according to their needs. The provisions that apply in this contract refer to the provisions of the general theory of the contract (naáº“riyyat al-'aqd) and are guided by the principle of freedom of contract (mabda' á¸¥urriyat at-ta'Äqud). An example of an unnamed contract is istishnÄ', bai al -wafa, istijrÄr, tahkÄ«r, book publishing contracts, advertising contracts, auction contracts, fiduciary contracts, leasing contracts, franchising contracts, consignment contracts, lease purchase agreements and others.